Analysis and modeling of the Lithuanian real estate sector - Zavadskas, Edmundas Kazimieras; Ginevičius, Romualdas; Kaklauskas, Artūras; Banaitis, Audrius (Journal of Business Economics and Management, 2005)
The model for an efficient real estate sector as suggested by this research is based on the presumption that the efficiency of a real estate sector depends on many macro and micro level variables. The presence of specific macro and micro level variable factors right away imposes objective limitations for efficient activities within the real estate sector. The real estate sector, in the presence of these objective limitations, tries to perform its functions within their bounds with the utmost efficiency. The research aimed at producing a model of a rational real estate sector by undertaking a complex analysis of micro and macro environment factors that affect it and to provide recommendations that would increase its competitive ability. In order to demonstrate the application of the above research by developing a model for an efficient real estate sector, a selection of rational housing investment instruments and lenders will be considered in this paper as a sample.First published online: 14 Oct 2010